Interactive ozone induces a negative feedback in CO2‐driven climate change simulations. Issue 4 (27th February 2014) - Dietmüller, S.; Ponater, M.; Sausen, R.
Abstract Interactively coupled climate chemistry models (CCMs) extend the number of feedback mechanisms in climate change simulations by including chemical feedback. In this study the radiative feedback from ozone changes on climate response and climate sensitivity is quantified for a series of simulations driven by CO2 increases on top of a present‐day reference concentration level. Other possibly relevant feedback via atmospheric chemistry, e.g., via CH4 and N2O, is not fully quantified in the CCM setup as their concentrations are essentially fixed at the surface. In case of a CO2‐doubling simulation, the ozone feedback reduces the climate sensitivity parameter by 3.4%, from 0.70 K/(W m−2) without interactive chemistry to 0.68 K/(W m−2). In case of a 4*CO2 simulation, the reduction of the climate sensitivity parameter increases to 8.4%. An analysis of feedback reveals that the negative feedback of stratospheric ozone and the associated negative feedback change in stratospheric water vapor are mainly responsible for this damping. The feedback from tropospheric ozone changes is positive but much smaller. The nonlinearity in the climate sensitivity damping with increased CO2 concentrations is shown to be due to nonlinear feedback of ozone and stratospheric water vapor.